1992
DOI: 10.1007/bf00316558
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure and movement of the ependymal and tracheal cilia in congenitally hydrocephalic WIC-Hyd rats

Abstract: The aim of the present investigation is to determine whether or not hydrocephalus occurring in hydrocephalic Wistar-Imamichi strain rats (WIC-Hyd) is caused by functional and structural disorders of ependymal cilia. Ultrastructures and movement of cilia in the ependyma of the lateral, III and IV ventricles and aqueduct of Sylvius and in the trachea walls of the animals were examined by means of scanning electron microscopy (SEM), transmission electron microscopy (TEM), and light microscopy using a phase-contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…The sparse cilia that were present were significantly smaller than cilia in wild-type mice, and appeared disorganized. It was also discovered during the analysis that Tg737 orpk mutants exhibit hydrocephalus, a phenotype often associated with left-right patterning abnormalities and ciliary defects on the ependymal cells (Shimizu and Koto, 1992;Nakamura and Sato, 1993;Chen et al, 1998). In all adult Tg737 orpk mutants analyzed, the ventricles were expanded relative to controls (Figure 8,C and D).…”
Section: Mutantsmentioning
confidence: 87%
See 1 more Smart Citation
“…The sparse cilia that were present were significantly smaller than cilia in wild-type mice, and appeared disorganized. It was also discovered during the analysis that Tg737 orpk mutants exhibit hydrocephalus, a phenotype often associated with left-right patterning abnormalities and ciliary defects on the ependymal cells (Shimizu and Koto, 1992;Nakamura and Sato, 1993;Chen et al, 1998). In all adult Tg737 orpk mutants analyzed, the ventricles were expanded relative to controls (Figure 8,C and D).…”
Section: Mutantsmentioning
confidence: 87%
“…Hydrocephalus results from increased intercranial pressure due to improper homeostasis or movement of the cerebral spinal fluid, and is often associated with ciliary abnormalities on ependymal cells lining the ventricles (Shimizu and Koto, 1992;Nakamura and Sato, 1993;Chen et al, 1998). Because these cells also express high levels of Tg737, we evaluated whether they have ciliary defects in Tg737 orpk mutants.…”
Section: Discussionmentioning
confidence: 99%
“…A central pair in 9+2 cilia may have more relevance to the cilia wave form. The beat pattern of 9+2 cilia has been described as a planar waveform (O'Callaghan et al, 1999;Shimizu and Koto, 1992;Smith and Yang, 2004). Zebrafish ependymal cilia and mouse node cilia beat in a simpler rotary pattern (McGrath et al, 2003).…”
Section: Motile Cilia In the Brain And Hydrocephalusmentioning
confidence: 99%
“…However, a recent study showed that ependymal ciliary beating was crucial for the formation of concentration gradients of CSF guidance molecules directing proper neuroblast migration (Sawamoto et al, 2006). The connection between ciliary function and CSF homeostasis has been clearly demonstrated, as ciliary dysfunction or immotility (Nakamura and Sato, 1993;Shimizu and Koto, 1992) as well as defects in ciliary structure components (Ibañez-Tallon et al, 2002;Ibañez-Tallon et al, 2004;Sapiro et al, 2002) or defects in proteins involved in ciliogenesis (Chen et al, 1998;Kobayashi et al, 2002;Taulman et al, 2001) may all result in hydrocephalus. Further, in patients with PCD, there are reports of associated enlarged ventricles and hydrocephalus (Ibañez-Tallon et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Ependymal cells bear approximately 40 motile cilia per cell which beat in the coordinated pattern at approximately 40 Hz (Del Bigio, 1995;O'Callaghan et al, 1999) that rapidly move CSF adjacent to the ventricular walls. The precise functional roles of ependymal cilia are not fully understood, however, it is known that abnormal ciliary function (Banizs et al, 2005;Mönkkönen et al, 2007;Shimizu and Koto, 1992), associated with an inherited condition known as Primary Ciliary Dyskinesia (PCD) can result in hydrocephalus (Ibañez-Tallon et al, 2004).…”
Section: Introductionmentioning
confidence: 99%